2010
DOI: 10.3109/07853890.2010.514285
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of celiac disease autoimmunity in a USA cohort followed since 1974

Abstract: During a 15-year period CD prevalence increased 2-fold in the CLUE cohort and 5-fold overall in the US since 1974. The CLUE study demonstrated that this increase was due to an increasing number of subjects that lost the immunological tolerance to gluten in their adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
253
1
15

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 342 publications
(273 citation statements)
references
References 31 publications
4
253
1
15
Order By: Relevance
“…Several studies in adults have identified individuals who were initially serologically negative but later developed a positive antibody. 7 In addition, our patient was under triple immunosuppressive treatment for renal transplant, which may have impaired the ability to produce antibodies. In addition to negative serology, there was no apparent micronutrient deficiency either.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in adults have identified individuals who were initially serologically negative but later developed a positive antibody. 7 In addition, our patient was under triple immunosuppressive treatment for renal transplant, which may have impaired the ability to produce antibodies. In addition to negative serology, there was no apparent micronutrient deficiency either.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the common susceptibility loci of HLA and other immune system-related genes, 3 permeability changes in the small-bowel mucosa, 4 and association with wheat consumption 4,5 are prominent. Both diseases are increasing in most regions of the world, 6,7 as are several other autoimmune diseases, but the actual cause of the disease remains unknown. However, several recent studies have highlighted the role of environmental and social changes that have taken place over the last several decades.…”
Section: Introductionmentioning
confidence: 99%
“…Необходимость анализа несколь-ких фрагментов слизистой кишки вытекает из мозаичности явлений атрофии при Ц. Отсутствие правильной ориента-ции гистологического материала (необходимо оценивать фрагменты вдоль длины ворсинки) может приводить к ложноположительным результатам за счет получения феномена «псевдоукорочения» ворсинок [1,3,4,9,10].…”
Section: ошибка 2 взятие недостаточного количества и отсут-ствие праunclassified